In vitro toxicity assessment of hydrogel patches obtained by cation‐induced cross‐linking of rod‐like cellulose nanocrystals. Issue 3 (27th May 2019) - Meschini, Stefania; Pellegrini, Evelin; Maestri, Cecilia Ada; Condello, Maria; Bettotti, Paolo; Condello, Giancarlo; Scarpa, Marina
Abstract: With the purpose of designing active patches for photodynamic therapy of melanoma, transparent and soft hydrogel membranes (HMs) have been fabricated by cation‐induced gelation of rod‐like cellulose nanocrystals (CNCs) bearing negatively charged carboxylic groups. Na +, Ca 2+, Mg 2+ have been used as cross‐linkers of cellulose nanocrystal (CNC). The biosafety of this material and of its precursors has been evaluated in vitro in cell cultures. Morphological changes, cell organelles integrity, and cell survival with the tetrazolium salt reduction (MTT) assay were utilized as tests of cytotoxicity. Preliminary investigation was performed by addition of the hydrogel components to the cell culture medium and by incubations of the CNC‐HM in direct and indirect contact with a confluent monolayer of A375 melanoma cells. Direct contact assays suffered from interference of physical stress. Careful evaluation of cytotoxicity was obtained considering the overall picture provided by microscopy and biochemical tests performed with the CNC‐HM in indirect contact with two melanoma cell lines (A375, M14) and human fibroblasts. CNCs have been demonstrated to be a safe precursor material and CNC‐HMs have a good biocompatibility provided that the excess of cations, in particular of Ca 2+ is removed. These results indicate that CNC and can be safely used to fabricate biomedical devices such as transparent hydrogel patches, although attention must be paid to the fabrication procedure.